The impact of surplus free cash flow and stock market segmentations on earnings management in Jordan: agency - and institutional - theory perspectives / Ahmad A. Toumeh, Sofri Yahya and Azlan Amran - Toumeh, Ahmad A.; Yahya, Sofri; Amran, Azlan (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2020)
The current research aims at providing evidence concerning the influence of surplus free cash flow (SFCF) and stock market segmentations (SMS) on income-increasing earnings management practices in Jordan. The results, based on a sample of all non-financial companies that were listed on the Amman Stock Exchange (ASE) from 2013 to 2017, confirm the research hypotheses. The Huber-White’s sandwich standard errors for randomeffects regression was used as the primary statistical tool for this study. The findings revealed a significant and positive association between SFCF and income-boosting discretionary accruals (DAC). As well, the results found that SMS was significantly and positively associated with the positive DAC. This research adds value to scholarship by investigating the impact of SMS variable on earnings management. To the best available knowledge, this relationship has not been examined either in Jordan or elsewhere in the world. Further, this is the first empirical attempt to investigate the effect of SFCF on earnings management in Jordan, which provides meaningful information for companies seeking to understand and reduce agency problems within the Jordanian context.